Angle-Weighted Reverse Time Migration With Wavefield Decomposition Based on the Optical Flow Vector - Xie, Chuang; Song, Peng; Li, Xishuang; Tan, Jun; Wang, Shaowen; Zhao, Bo (Frontiers in Earth Science, 2021)
Reverse time migration (RTM) is based on the two-way wave equation, so its imaging results obtained by conventional zero-lag cross-correlation imaging conditions contain a lot of low-wavenumber noise. So far, the wavefield decomposition method based on Poynting vector has been developed to suppress these noises, however, this method also has some problems, such as unstable calculation of Poynting vector, low accuracy of wavefield decomposition, and poor effect of large-angle migration noise suppression. This paper introduces the optical flow vector method to RTM to realize high-precision wavefield decomposition for both the source and receiver wavefields, and obtains four directions of wavefields: up-, down-, left- and right-going. Then the cross-correlation imaging sections of one-way propagation components of forward- and back-propagated wavefields are optimized and stacked. On this basis, the reflection angle of each imaging point underground is calculated based on the optical flow vector, and an attenuation factor related to the reflection angle is introduced as the weight to generate the optimal stack section. The test of theoretical model illustrates that compared with the conventional RTM with wavefield decomposition based on Poynting vector, the angle-weighted RTM with wavefield decomposition based on optical flow vector proposed in this paper can achieve wavefield decomposition both for the source and receiver wavefields, and calculate the reflection angle of each imaging point more accurately and stably. Moreover, the proposed method adopts angle weighting processing, which can further implement the attenuation of large-angle migration noise and effectively improve the imaging accuracy of RTM.